2013
DOI: 10.1007/s40436-013-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optimization of multiple performance characteristics in WEDM for machining ZC63/SiCp MMC

Abstract: The compliance of an integrated approach, principal component analysis (PCA), coupled with Taguchi's robust theory for simultaneous optimization of correlated multiple responses of wire electrical discharge machining (WEDM) process for machining SiC P reinforced ZC63 metal matrix composites (MMCs) is investigated in this work. The WEDM is proven better for its efficiency to machine MMCs among others, while the particulate size and volume percentage of SiC p with the composite are the utmost important factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The findings of magnesium alloy in view of efficient machining operation with different facets of the performance and reliability of the magnesium alloy are discussed using wire-EDM [18], [19]. The findings of an experimental study on the selection of processing conditions that decide performance of wire-EDM using aluminium alloy and the optimization abilities of some output responses in wire-EDM of reinforced ZC63 metal matrix composite are discussed [20], [21]. Experimental investigation of performance measures using wire-EDM for alumium alloy-7017 and rolled homogeneous armor (RHA) steel shows favourable value [22].…”
Section: Related Workmentioning
confidence: 99%
“…The findings of magnesium alloy in view of efficient machining operation with different facets of the performance and reliability of the magnesium alloy are discussed using wire-EDM [18], [19]. The findings of an experimental study on the selection of processing conditions that decide performance of wire-EDM using aluminium alloy and the optimization abilities of some output responses in wire-EDM of reinforced ZC63 metal matrix composite are discussed [20], [21]. Experimental investigation of performance measures using wire-EDM for alumium alloy-7017 and rolled homogeneous armor (RHA) steel shows favourable value [22].…”
Section: Related Workmentioning
confidence: 99%
“…In another effort in 2013, Rajyalakshmi and Venkata Ramaiah, performed a multi-objective optimization for parts made of Inconel 825 with machine settings as independent variables and MRR, SR, and spark gap (SG) as dependent variables [11]. In the same year, Rao and Krishna studied the best input settings to optimize the values of wire wear and kerf width using harmony search for ZC63/SiCp MMC [12]. Also, Durairaj et al optimized SR and Kerf by using GRA [13], and then Shayan and others by applying RSM for SR, overcut, and cutting speed [14].…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes revealed that the WEDM responses were influenced by the POT, POFT, and CA, respectively. Additionally, the R a , one of the most important indicators of the surface integrity was optimized in conjunction with other factors, including the cutting speed (CS) [8], wire wear ratio (WWR) [9], kerf width (KW) [10][11][12], and material removal rate (MRR) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the effects of the varied conditions on machining responses for different WEDM operations have been performed. Different optimization techniques, such as the RSM [1,2,4,[6][7][8][9]13], Taguchi [3,14], grey relation analysis (GRA) [15], and hybrid approach [9,10,12] were utilized to resolve the optimizing issues. However, the published works regarding optimization in the WEDM performances have still the limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation